The Influence of Social Capital and Fear of Covid-19 on the Participation of Coastal Communities During the Pandemic in Palu City - Haslinda Badji Anriani; Muhammad Ahsan Samad; Muhammad Alfian (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
The advent of the Covid-19 pandemic has engendered multifaceted repercussions encompassing the economic, social, and psychological dimensions of coastal towns. In response, a proactive and concerted effort is imperative to cultivate a resilient society capable of withstanding the adversities posed by the Covid-19 pandemic. This necessitates the systematic integration of coastal communities through a scientific approach. This research elucidates the intricate interplay between social capital, apprehensions regarding Covid-19, and their combined influence on the determinants of community engagement. By means of an online survey, a cohort of 303 urban communities residing in the coastal regions of Palu-Donggala actively partook in this investigation. The outcomes of this study underscore the discernible impacts of both social capital and Covid-19-related concerns on the level of participation exhibited by coastal communities. The empirical insights gleaned from this study are poised to serve as a foundational resource for diverse stakeholders engaged in formulating interventions and policies aimed at augmenting community involvement within coastal enclaves. It is essential to acknowledge that further research endeavors are warranted to comprehensively discern the array of predictors underpinning and the far-reaching consequences of participatory behavior within coastal communities.